CYBER ATTACKS ON GOVERNMENT-MANAGED SYSTEMS: A SOCIAL EPISTEMOLOGY PERSPECTIVE - Romavella, Aurelia Bunga Anggun Putri; Hadinata, Fristian (UI Scholars Hub, 2025)
This article examines cyberattacks on government-managed systems from the perspective of social epistemology. The development of information technology, particularly the internet, has changed the way governments operate and interact with the public. However, these changes have also created new vulnerabilities to cyberattacks that can disrupt public services, undermine public trust and threaten national security. Social epistemology, with its focus on how knowledge and beliefs are constructed and disseminated in society, provides a useful analytical framework for understanding these cyberattack dynamics. This article examines how cyberattacks affect the production, distribution and validation of knowledge in the context of governance. By analyzing how different actors, including governments, hackers, and the public, interact and form a shared understanding of threats and cybersecurity, this article aims to provide insights on how to build more effective cybersecurity strategies and improve the resilience of government systems to cyberattacks. In addition, this article will also discuss the philosophical implications of cyberattacks, specifically related to the thoughts of Heidegger, Latour, Clark, and Postman, to understand how technology shapes social and political interactions in the context of cybersecurity. Effective IT governance, which integrates socio-technical understanding, is crucial in mitigating risks and building public trust in the digital age.